Non-Levallois bifacial assemblages with Levallois cores – an eastern "anomaly" into a nice picture - Vladimir B. Doronichev; Liubov V. Golovanova (UISPP Journal)
In the eastern part of Europe, from the Carpathians in the west to the Caucasus in the south and the Volga River in the east, a number of sites have yilded lithic assemblages with bifacial leaf points and bifacial asymmetric knives, dating from OIS 7 to OIS 5 and representing the Early Middle Palaeolithic (EMP) Leaf Point industry. The results of technological analyses indicate that the flaking technology in these EMP assemblages is not aimed at production of either laminar or Levallois blanks from prepared cores, despite the assemblages often contain a significant number of cores that can be classified as recurrent or preferential Levallois cores, using formal typological definitions. This eastern "anomaly" should prompt us to rethink the existing division between prepared and unprepared cores, taking in mind that similar types of cores may appear in different phases of their reduction within very different flaking technologies. The eastern "anomaly" also should prompt us to reformate the analysis and definition of knapping products and flaking technologies in the Lower and Middle Palaeolithic contexts, pointing to that the modern approach should be based on a comprehensive research of technological relationships between the core reduction sequence and the blank production sequence.